2018
DOI: 10.1002/ncp.10022
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malnutrition Evaluated by Mini Nutritional Assessment and Sarcopenia in Noninstitutionalized Elderly People

Abstract: MNA score is low in noninstitutionalized elderly subjects with sarcopenia, and it is linearly related to muscle mass and muscle strength. These data indicate that MNA score, when evaluated with muscle mass and strength, may recognize elderly subjects with sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
6
31
0
3
Order By: Relevance
“…Malnutrition indices and sarcopenia in community-dwelling elderly are poorly investigated, and the result is still controversial. One study conducted in a geriatric outpatient population showed that the parameters for malnutrition, including the Short Nutritional Assessment Questionnaire (SNAQ), loss of appetite, unintentional weight loss, and BMI < 22 kg/m 2 , were not consistently associated with diagnostic measures of sarcopenia 29 , while other studies demonstrated that malnutrition diagnosed by the MNA, the Global Leadership Initiative of Malnutrition (GLIM), and the European Society of Clinical Nutrition and Metabolism (ESPEN) criteria were a significant risk factor for sarcopenia 30,31 . The non-statistically significant result for BMI and malnutrition in our study may be attributable to the small sample size, which could have the effect of underpowering the study.…”
Section: Discussionmentioning
confidence: 97%
“…Malnutrition indices and sarcopenia in community-dwelling elderly are poorly investigated, and the result is still controversial. One study conducted in a geriatric outpatient population showed that the parameters for malnutrition, including the Short Nutritional Assessment Questionnaire (SNAQ), loss of appetite, unintentional weight loss, and BMI < 22 kg/m 2 , were not consistently associated with diagnostic measures of sarcopenia 29 , while other studies demonstrated that malnutrition diagnosed by the MNA, the Global Leadership Initiative of Malnutrition (GLIM), and the European Society of Clinical Nutrition and Metabolism (ESPEN) criteria were a significant risk factor for sarcopenia 30,31 . The non-statistically significant result for BMI and malnutrition in our study may be attributable to the small sample size, which could have the effect of underpowering the study.…”
Section: Discussionmentioning
confidence: 97%
“… 5 – Growth factors involved in muscle growth regulation, such as myostatin (MYO), activine A and B, growth differentiation factor-15 (GDF-15), bone morphogenetic proteins (BMPs), members of TGF-β family; 72 76 TGF-β itself; 76 follistatin (FST; the main inhibitor of MYO), 77 and brain-derived neurotrophic factor (BDNF); 78 – Markers of muscle protein turnover including neoepitopes, such as sarcomeric proteins (actin, myosin, troponin, and tropomyosin) and extracellular matrix proteins as well as type VI collagen N-terminal globular domain epitope (IC6), MMP-generated degradation fragment of collagen 6 (C6M), N-terminal peptide (P3NP); 79 , 80 3-methylhistidine (3MH), skeletal muscle-specific isoform of troponin T (sTnT), and creatinine. 5 – Markers of physical inactivity such as complement protein C1q, hemoglobin, albumin, selenium, leptin, uric acid, magnesium, and vitamin D. 81 88 – Markers of inflammation and oxidative stress: IL-6, IL-1, TNF-α, butyryl-cholinesterase (b-CHE), oxidized low density lipoprotein (OxLDL), and vitamins C and E. 89 93 …”
Section: Definition Of Sarcopeniamentioning
confidence: 99%
“…– Markers of physical inactivity such as complement protein C1q, hemoglobin, albumin, selenium, leptin, uric acid, magnesium, and vitamin D. 81 88 …”
Section: Definition Of Sarcopeniamentioning
confidence: 99%
“…Patients with severe HF frequently suffer from a gastroenteropathy secondary to intestinal edema which causes malabsorption and anorexia. Anorexia, independently associated with decreased muscle mass and strength [31,32], is a common symptom in HF because it is also related to dysgeusia and nausea, frequent side effects of drugs commonly prescribed in this disease (i.e., digoxin, angiotensin-converting enzyme (ACE) inhibitors, β-blockers, and diuretics). This list can also be responsible of a loss of nutrients through urination [33].…”
Section: Malnutrition and Malabsorptionmentioning
confidence: 99%